2012
DOI: 10.1371/journal.pcbi.1002637
|View full text |Cite
|
Sign up to set email alerts
|

Gene Network Homology in Prokaryotes Using a Similarity Search Approach: Queries of Quorum Sensing Signal Transduction

Abstract: Bacterial cell-cell communication is mediated by small signaling molecules known as autoinducers. Importantly, autoinducer-2 (AI-2) is synthesized via the enzyme LuxS in over 80 species, some of which mediate their pathogenicity by recognizing and transducing this signal in a cell density dependent manner. AI-2 mediated phenotypes are not well understood however, as the means for signal transduction appears varied among species, while AI-2 synthesis processes appear conserved. Approaches to reveal the recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Moreover, its signal transduction cascade is evolutionarily extensive and mechanistically diverse (Quan and Bentley, 2012). Hence, one's ability to conceive of and engineer a system for a particular application is substantial when based on AI-2.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, its signal transduction cascade is evolutionarily extensive and mechanistically diverse (Quan and Bentley, 2012). Hence, one's ability to conceive of and engineer a system for a particular application is substantial when based on AI-2.…”
Section: Introductionmentioning
confidence: 99%
“…AI-2 production has been verified in over 80 species, and AI-2 controls gene expression in a variety of bacteria. By using Local Modular Network Alignment Similarity Tool (LMNAST) to study gene order and generate homologous loci, the AI-2/Lsr system was reported to be phylogenetically more dispersed than the well-studied lac operon, while its distribution remained densest among gammaproteobacteria [64]. These findings together reinforced the hypothesis that bacteria use AI-2 to communicate between species [31,65].…”
Section: Universal Autoinducer Ai-2mentioning
confidence: 77%
“…Here, we target autoinducer‐2 (AI‐2) by the incorporation of a natural enzyme that modifies the autoinducer to its phosphorylated form, preventing its uptake (Kamaraju et al, ) into bacteria that employ the Lsr signal transduction cascade (Quan & Bentley, ; Roy et al, ). AI‐2 was chosen for several reasons: it is used in signaling among Gram‐positive and Gram‐negative bacteria (Pereira et al, ; Quan & Bentley, ), it is not produced by eukaryotic cells (Vendeville, Winzer, Heurlier, Tang, & Hardie, ) and apparently has minimal effect on gastrointestinal epithelial cells (Zargar, Quan, Carter, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we target autoinducer-2 (AI-2) by the incorporation of a natural enzyme that modifies the autoinducer to its phosphorylated form, preventing its uptake (Kamaraju et al, 2011) into bacteria that employ the Lsr signal transduction cascade (Quan & Bentley, 2012;Roy et al, 2009). AI-2 was chosen for several reasons: it is used in signaling among Gram-positive and Gram-negative bacteria (Pereira et al, 2013;Quan & Bentley, 2012), it is not produced by eukaryotic cells (Vendeville, Winzer, Heurlier, Tang, & Hardie, 2005) and apparently has minimal effect on gastrointestinal epithelial cells (Zargar, Quan, Carter, et al, 2015). Also, the mechanism of AI-2 phosphorylation is relatively well understood (Zhu, Hixon, Globisch, Kaufmann, & Janda, 2013) and previous work has demonstrated that interfering with AI-2 can alter QS communication in "synthetic ecosystems" (Roy, Adams, & Bentley, 2011;Roy et al, 2009Roy et al, , 2010 or otherwise influence biofilm formation and clearance when used in combination with antibiotics (Roy et al, 2013).…”
mentioning
confidence: 99%